2022
DOI: 10.3389/fped.2022.867767
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Time Interval Between First Extubation and Reintubation on Bronchopulmonary Dysplasia or Death in Very Low Birth Weight Infants

Abstract: ObjectiveTo explore the association between time from first extubation to reintubation and moderate-to-severe bronchopulmonary dysplasia (BPD) or death in very low birth weight infants.Study DesignInfants weighing <1,500 g at birth, requiring mechanical ventilation, and undergoing their initial extubation were retrospectively included from January 2014 to December 2021. They were divided into the moderate-to-severe BPD/death group and the comparison group according to the incidence of moderate-to-severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…An association between reintubation within 72 hrs of extubation and increased likelihood of moderate-to-severe BPD or death in very low birth weight infants was reported [ 44 ] Here, we found that NHFOV probably reduces the risk of extubation failure or reintubation within 72 hrs in NICU patients when compared to NCPAP or NIPPV. The decreased rate of reintubation probably played a role in the lower occurrence of BPD in neonates receiving NHFOV.…”
Section: Discussionsupporting
confidence: 56%
“…An association between reintubation within 72 hrs of extubation and increased likelihood of moderate-to-severe BPD or death in very low birth weight infants was reported [ 44 ] Here, we found that NHFOV probably reduces the risk of extubation failure or reintubation within 72 hrs in NICU patients when compared to NCPAP or NIPPV. The decreased rate of reintubation probably played a role in the lower occurrence of BPD in neonates receiving NHFOV.…”
Section: Discussionsupporting
confidence: 56%
“…Subgroup analysis of two large randomized controlled trials showed that reintubation within 5 and 7 days after extubation is associated with an increased incidence of respiratory diseases including BPD 28 , 29 . But, a single-center retrospective study (n = 244) from Li et al found that reintubation was not an independent risk factor for moderate-to-severe BPD (for reintubations occurring within 72 h after extubation, adjusted OR = 1.714, 95% CI 0.546–5.374; for reintubations occurring within 7 d after extubation, adjusted OR = 1.501, 95% CI 0.482–4.678) 30 . Shalish W et al found that reintubation within observation windows ranging from 24 h to 3 weeks post-extubation was not associated with the increased ORs of BPD among survivors 19 .…”
Section: Discussionmentioning
confidence: 98%
“…Reintubation within 72 h of initial extubation in very low or extremely low birth weight infants was independently associated with increased risk of BPD/death and death in a retrospective cohort study ( 20 ). This result is consistent with a multicenter observational study ( 21 ) that demonstrated that for preterm infants, reintubation after elective extubation was an independent risk factor for death or moderate to severe BPD, especially reintubation within 48 h of extubation.…”
Section: Discussionmentioning
confidence: 99%